2019
DOI: 10.1142/s0218216519400182
|View full text |Cite
|
Sign up to set email alerts
|

New skein invariants of links

Abstract: We introduce new skein invariants of links based on a procedure where we first apply the skein relation only to crossings of distinct components, so as to produce collections of unlinked knots. We then evaluate the resulting knots using a given invariant. A skein invariant can be computed on each link solely by the use of skein relations and a set of initial conditions. The new procedure, remarkably, leads to generalizations of the known skein invariants. We make skein invariants of classical links, H[R], K[Q]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 61 publications
(148 reference statements)
1
11
0
Order By: Relevance
“…Comparing (6.12) and (6.13) to Remarks 8 and we deduce that {{L}} coincides with the invariant V [V ] in the notation of [27] and, thus, we recover the invariant θ(q, E). Hence we have proved the following:…”
Section: 4supporting
confidence: 60%
See 3 more Smart Citations
“…Comparing (6.12) and (6.13) to Remarks 8 and we deduce that {{L}} coincides with the invariant V [V ] in the notation of [27] and, thus, we recover the invariant θ(q, E). Hence we have proved the following:…”
Section: 4supporting
confidence: 60%
“…The cornerstone of this construction is the 3-variable generalization Θ of the invariants Θ d constructed in [4] and which will be presented here. The well-definedness of Θ has been proved both algebraically [4] and skein-theoretically [27,28]. We will present all approaches, as they are all very informative.…”
Section: The Invariant θ and The Algebra Of Braids And Tiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the same skein relation as the one satisfied by the Jones polynomial holds, but only on crossings between different components; we call these crossings mixed crossings. Using a recursive proof method developed originally by Lickorish-Millett [12] and adapted for θ by Kauffman-Lambropoulou [9], it can be shown that calculating the value of θ on a link L amounts to calculating the value of θ on links that are unions of unlinked knots and are obtained via the skein relation. More specifically, a series of switchings and smoothings of mixed crossings transforms the initial link to a family of unions of unlinked knots, called descending stacks.…”
Section: Introductionmentioning
confidence: 99%